If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13x + -1(19) = -6 Multiply -1 * 19 -13x + -19 = -6 Reorder the terms: -19 + -13x = -6 Solving -19 + -13x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '19' to each side of the equation. -19 + 19 + -13x = -6 + 19 Combine like terms: -19 + 19 = 0 0 + -13x = -6 + 19 -13x = -6 + 19 Combine like terms: -6 + 19 = 13 -13x = 13 Divide each side by '-13'. x = -1 Simplifying x = -1
| X^2+5x+6=42 | | 4y=7+8x | | 25=s+13-45s | | 12=-8t^2+24t+5 | | Y+30= | | -4=(6-2x) | | 5.5(2w+9)=23.1 | | h(t)=-8t^2+24t+5 | | (2n+12n)-5(-2.4n+4)= | | 3.4(k-7)=5.1 | | 15p-9=5p-35 | | 2.4c-3.5+4.7=10.8 | | 30=50d-8 | | -4p+7+5p=14 | | X+10.7=20.33 | | x+78=14 | | 5p+7=14 | | 0.9x+0.1=2.8 | | (2n+12n)-(-9+20)= | | Bbb/bbbbb | | arctan(x/y)=45 | | -8-20n=0 | | 10(2.2-10b)=15.2 | | -2/-9g=-7/-9 | | H(1)=-5 | | 3z-4=4 | | 2+5/12=-3+1/4+x | | 2x+32+3x+30=113 | | (1+xy)xdy+(1-xy)ydx=0 | | -0.6x-2=1 | | Z^2+5z+6=42 | | 28+6(2x+4)=124 |